Preparation method of low-temperature sintered high-purity alumina ceramic

The α-Al2O3 powder with interlocking hexagonal morphology was prepared by the aluminum sol method, and the sheet-like structure was used for low-temperature sintering, which solved the problem of high sintering temperature and high cost of alumina ceramics in the prior art, and achieved low-cost and simple process preparation of high-purity alumina ceramics, and improved the mechanical and thermal properties of the ceramics.

CN120172729AActive Publication Date: 2025-06-20JINGDEZHEN CERAMIC UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510675756.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-06-20
Estimated Expiration
2045-05-23

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high-purity alumina ceramics at low cost and simple processes, especially under low-temperature sintering conditions, which have problems such as high sintering temperature, long time, high cost and uneven structure.

Method used

The interlocking hexagonal morphology of α-Al2O3 powder was prepared by the aluminum sol method, and the ceramic powder with a sheet-like structure was sintered for low temperature sintering, and the interlaced network structure was formed using the characteristics of porous and micro-nano structures to reduce the sintering temperature and cost.

Benefits of technology

The preparation of low-temperature sintered high-purity alumina ceramics is realized, which improves the mechanical strength, fracture toughness and thermal conductivity of the ceramics, while reducing water absorption and shrinkage, improving processing performance. It also has a simple process and low equipment requirements, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120172729A_ABST
    Figure CN120172729A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of low-temperature sintered high-purity alumina ceramic, which comprises the following steps: step 1, mixing alumina sol, sodium sulfate, aluminum fluoride and water according to the mass percent of 1: (1-3): (0.08-0.18): (1-2) to form turbid liquid, heating, stirring, drying, grinding, sieving and calcining the turbid liquid to obtain alpha-Al2O3 powder; and 2, grinding the alpha-Al2O3 powder prepared in the step 1, sieving, granulating, forming, drying and calcining to obtain the alpha-Al2O3 ceramic. The temperature of the calcining procedure in the step 1 is 1000-1200 DEG C, the heat preservation time is 1-3 hours, and the heating rate is 3-5 DEG C / min. According to the invention, the sintering temperature of the high-purity alumina is greatly reduced, the product has lower water absorption and shrinkage, and the preparation method is simple and convenient, easy to control and easy for large-scale production, so that the preparation method has a great industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic material preparation, and particularly relates to a method for preparing a low-temperature sintered high-purity alumina ceramic. Background Art

[0002] Alumina ceramics have characteristics such as high mechanical strength, high hardness, good high-temperature insulation performance, and corrosion resistance, and are widely used in fields such as machinery, electronics, and chemical engineering. However, for single-phase alumina ceramics, the melting point is as high as 2050 °C, the material is bonded in the form of ionic bonds or covalent bonds, the diffusion coefficient of the particles is small, the sintering temperature exceeds 1750 °C, and a long sintering time is required, resulting in low production efficiency and high costs. In addition, during the high-temperature sintering process, growth anisotropy and abnormal grains are likely to occur, resulting in non-uniform structure, and even residual pores inside, reducing the bonding strength between grains and causing a significant decline in material properties. Therefore, it is still a huge challenge to prepare high-density alumina ceramics in a simple, reliable, and low-cost manner.

[0003] At present, there are mainly three methods to reduce the sintering temperature of alumina ceramics: (1) Controlling the particle size: By reducing the particle size of alumina powder, such as using nano-scale ceramic powder to reduce the initial size of grains, the final sintered product maintains microcrystalline characteristics. And based on its unique nano-scale effects such as high specific surface area, the sintering activity of the ceramic substrate is significantly improved. However, the use of nano-scale alumina powder is expensive and the production cost is high; the conditions required for special processes are complex and the production efficiency is low. There are problems such as inability to mass-produce and high costs. Especially in recent years, with the ultra-fine development of raw material particle size, the firing shrinkage rate of alumina ceramic products has gradually increased from about 17% to about 23%, resulting in a series of problems such as product deformation, cracking, increased machining allowance and difficulty in production; (2) Adopting other advanced sintering technologies: Such as hot isostatic pressing sintering, spark plasma sintering, pulsed current sintering or microwave sintering, which can increase the sintering driving force and achieve densification in a shorter time. But it has high requirements for equipment and high costs. (3) Adding sintering aids: Sintering aids can form solid solutions with alumina, increase lattice distortion, and improve the diffusion rate, thereby reducing the sintering temperature of alumina ceramics. Common ones are MnO, TiO2, Fe2O3, etc. They have lattice constants similar to alumina and can form different types of solid solutions with alumina. In addition, the additive itself or between the additive and the alumina matrix can form a liquid phase at high temperature, and promote sintering through the dissolution-precipitation mechanism, that is, when the sintering temperature reaches the melting point or eutectic temperature of the additive, a liquid phase begins to appear, promoting the migration and diffusion of particles in the sintered body and improving the sintering performance of alumina ceramics. Common sintering aids reduce the sintering temperature to 1500-1700°C, and there is still a large room for improvement. And the addition of sintering aids such as TiO2 promotes the formation of anisotropic grains with large aspect ratios, significantly affecting the microstructure of alumina ceramics and resulting in anisotropy of the ceramic itself, with greater restrictions on the use method. To sum up, these three methods have problems such as complex preparation and high costs. Therefore, it is particularly important to seek a preparation method with low cost. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method for low-temperature sintering high-purity alumina ceramics with low cost, simple process and suitable for large-scale production.

[0005] To solve the above technical problems, the technical solution of the present invention is: A preparation method for low-temperature sintering high-purity alumina ceramics, which is characterized by including the following steps: Step 1: Dissolve aluminum sol, sodium sulfate, and aluminum fluoride in water according to mass percentages to obtain a suspension. After the suspension undergoes heating, stirring, drying, grinding, sieving, and calcination processes, α-Al2O3 powder is obtained; Step 2: The α-Al2O3 powder obtained in Step 1 is subjected to grinding, sieving, granulation, forming, drying, and calcination processes to obtain α-Al2O3 ceramics.

[0006] In Step 1, the mass ratio of aluminum sol, sodium sulfate, aluminum fluoride, and water is 1:1 - 3:0.08 - 0.18:1 - 2.

[0007] The mass percentage composition of the aluminum sol is: 20.243 wt% Al2O3, 0.012 wt% SiO2, 0.003 wt% Fe2O3, 0.012 wt% Na2O, 79.73 wt% ethanol organic solvent.

[0008] In Step 1, the temperature of the heating and stirring process is 60 - 95°C; the temperature of the drying process is 80 - 100°C, and the heat preservation time is 5 - 8 h; the sieving process is through a 200 - 325 mesh sieve.

[0009] In Step 1, the temperature of the calcination process is 1000 - 1200°C, the heat preservation time is 1 - 3 h, and the heating rate is 3 - 5°C / min.

[0010] In Step 2, the sieving process is through a 350 - 400 mesh sieve; the forming process is dry pressing, and the pressure is 18 - 21 MPa; the temperature of the drying process is 60 - 100°C, and the heat preservation time is 30 - 45 min.

[0011] In the granulation process of Step 2, PVA is added as a binder, and its mass is 1 - 3% of the α-Al2O3 powder, and the mass concentration is 3 - 5%.

[0012] In Step 2, the firing temperature of the calcination process is 1350°C, the heating rate is 2 - 10°C / min, and the heat preservation time is 30 - 120 min.

[0013] The particle size of the α-Al2O3 powder in Step 1 is 1 - 5 μm, the specific surface area is 1 - 5 m 2 / g, the average pore diameter is 45 - 60 nm, the morphology is flaky hexagonal, the powders are interlocked with each other, and the aspect ratio of diameter to thickness is 8 - 10:1.

[0014] The alumina content of the α-Al2O3 ceramics in Step 2 is 98.55 - 99.25 wt%, the density is 3.59 - 3.62 g / cm 3 , the shrinkage rate is 1 - 1.2%, and the flexural strength is 204 - 219 MPa.

[0015] The present invention has the following beneficial effects: The present invention successfully prepares alumina ceramics from interlocked hexagonal α-Al2O3 powder prepared by the aluminosol method. Using a flaky interlocked hexagonal morphology and taking advantage of its porous and micro-nano structure characteristics, an interlaced network structure can be formed during the sintering process, which helps to improve the mechanical strength and fracture toughness of the ceramics. Secondly, the flaky structure helps to improve the thermal conductivity of the ceramics because the flaky particles are arranged parallel in the sintered body, forming a better heat conduction path, thereby reducing the sintering temperature of the alumina ceramics. And the sample has a low water absorption rate and shrinkage rate, greatly reducing the firing deformation degree of the product and improving the processing performance of the product. This preparation process is simple and convenient, requires low equipment requirements, is easy to control and scale up production, and has great industrialization prospects. Description of the Drawings

[0016] Figure 1 It is the BET and pore size diagram of the flaky interlocked hexagonal α-Al2O3 powder prepared in Example 1; Figure 2 It is the SEM diagram of the α-Al2O3 alumina ceramic prepared in Example 1; Figure 3 It is the XRD diagram of the α-Al2O3 alumina ceramic prepared in Example 1; Figure 4 It is the performance curve comparison between the α-Al2O3 alumina ceramic prepared in Example 1 and the alumina ceramic currently used in industry. Detailed Description of the Invention

[0017] The present invention will be further described in detail below with reference to the drawings and specific embodiments.

[0018] Example 1

[0019] A preparation method of low-temperature sintered high-purity alumina ceramics includes the following steps: Step 1: Add aluminosol, sodium sulfate and aluminum fluoride mineralizer into water to obtain a suspension. Among them, the mass ratio of aluminosol: sodium sulfate: aluminum fluoride: water is 1:1:0.16:1. Heat and stir the suspension at 60°C. After the suspension gradually becomes paste-like, place it in an oven and dry it at 80°C for 5 hours. Keep it warm for 5 hours, grind it, pass through a 250-mesh sieve, obtain the precursor, place it in a muffle furnace, the calcination temperature is 1100°C, keep it warm for 1 hour, and the heating rate is 5°C / min to obtain white α-Al2O3 powder; Step 2: Grind the powder in Step 1 sufficiently, and then pass through a 400-mesh sieve; Step 3: Select PVA with a mass concentration of 5% as the binder after grinding in Step 2, with a mass of 2% of the α-Al2O3 powder, and add it to the α-Al2O3 powder for granulation; Step 4: The powder obtained after granulation in Step 3 is dry-pressed into a green body at a forming pressure of 21 MPa, and the obtained green body is placed in an oven and kept at 60 °C for 45 min; Step 5: The green body dried in Step 4 is calcined at a firing temperature of 1350 °C, a heating rate of 3 °C / min, and a holding time of 120 min.

[0020] The particle size of the white α-Al2O3 powder prepared in Step 1 is 1 μm, the specific surface area is 5 m 2 / g, the average pore diameter is 45 nm, and its morphology is sheet-like hexagonal and interlocked with each other, and the aspect ratio is about 10:1.

[0021] The α-Al2O3 ceramic prepared in Step 5 has an alumina content of 99 wt%, a density of 3.60 g / cm 3 , a shrinkage rate of 1%, and a flexural strength of 204 MPa.

[0022] Example 2

[0023] A preparation method of a low-temperature sintered high-purity alumina ceramic, comprising the following steps: Step 1: Add aluminum sol, sodium sulfate and aluminum fluoride mineralizer to water to obtain a suspension. Among them, the mass ratio of aluminum sol: sodium sulfate: aluminum fluoride: water is 1:3:0.18:2. The suspension is heated and stirred at 95 °C. After the suspension gradually becomes paste-like, it is placed in an oven and dried at 100 °C for 8 h, kept warm for 8 h, ground, passed through a 200-mesh sieve, and the obtained precursor is placed in a muffle furnace. The calcination temperature is 1200 °C, the holding time is 1 h, and the heating rate is 3 °C / min to obtain white α-Al2O3 powder; Step 2: Grind the powder in Step 1 sufficiently and then pass it through a 350-mesh sieve; Step 3: Select PVA with a mass concentration of 3% as the binder in Step 2, with a mass of 3% of the α-Al2O3 powder, and add it to the α-Al2O3 powder for granulation; Step 4: The powder obtained after granulation in Step 3 is dry-pressed into a green body at a forming pressure of 18 MPa, and the obtained green body is placed in an oven and kept at 100 °C for 30 min; Step 5: The green body dried in Step 4 is calcined at a firing temperature of 1350 °C, a heating rate of 5 °C / min, and a holding time of 100 min.

[0024] The particle size of the white α-Al2O3 powder prepared in Step 1 is 5 μm, the specific surface area is 1 m 2 / g, the average pore diameter is 60 nm, and its morphology is sheet-like hexagonal and interlocked with each other, and the aspect ratio is about 9:1.

[0025] The α-Al2O3 ceramic prepared in Step Five has an alumina content of 99 wt% and a density of 3.59 g / cm 3 , a shrinkage rate of 1.2%, and a flexural strength of 215 MPa.

[0026] Example 3

[0027] A preparation method of a low-temperature sintered high-purity alumina ceramic, comprising the following steps: Step One: Add aluminum sol, sodium sulfate, and aluminum fluoride mineralizer into water to obtain a suspension. Among them, the mass ratio of aluminum sol:sodium sulfate:aluminum fluoride:water is 1:2:0.1:1.5. Heat and stir the suspension at 85 °C. After the suspension gradually becomes paste-like, place it in an oven and dry it at 90 °C for 8 h of heat preservation. Grind it, pass through a 325-mesh sieve, and obtain a precursor. Place it in a muffle furnace, the calcination temperature is 1100 °C, keep the temperature for 2 h, and the heating rate is 4 °C / min to obtain white α-Al2O3 powder; Step Two: Grind the powder in Step One sufficiently, and then pass through a 400-mesh sieve; Step Three: Select PVA with a mass concentration of 5% as the binder, which is 1% of the mass of the α-Al2O3 powder, and add it to the α-Al2O3 powder for granulation; Step Four: Dry-press the granulated powder in Step Three, the forming pressure is 20 MPa, obtain a green body, and place it in an oven to keep the temperature at 100 °C for 40 min; Step Five: Calcinate the dried green body in Step Four, the firing temperature is 1350 °C, the heating rate is 10 °C / min, and the heat preservation time is 70 min.

[0028] The particle size of the white α-Al2O3 powder prepared in Step One is 3 μm, the specific surface area is 3 m 2 / g, the average pore diameter is 50 nm, its morphology is sheet-like hexagonal, and they are interlocked with each other, and the aspect ratio is about 8:1.

[0029] The α-Al2O3 ceramic prepared in Step Five has an alumina content of 98.55 wt% and a density of 3.59 g / cm 3 , a shrinkage rate of 1%, and a flexural strength of 214 MPa.

[0030] Example 4

[0031] A preparation method of a low-temperature sintered high-purity alumina ceramic, comprising the following steps: Step 1: Add aluminum sol, sodium sulfate, and aluminum fluoride mineralizer into water to obtain a suspension. Among them, the mass ratio of aluminum sol:sodium sulfate:aluminum fluoride:water is 1:1:0.08:2. Heat and stir the suspension at 95 °C. After the suspension gradually becomes paste-like, place it in an oven and dry it at 100 °C for 5 h, keep it warm for 5 h, grind it, pass through a 250-mesh sieve, obtain the precursor, place it in a muffle furnace, the calcination temperature is 1000 °C, keep it warm for 3 h, and the heating rate is 3 °C / min to obtain white α-Al2O3 powder; Step 2: Grind the powder in Step 1 thoroughly, and then pass through a 400-mesh sieve; Step 3: After grinding in Step 2, select PVA with a mass concentration of 4% as the binder, with a mass of 2% of the α-Al2O3 powder, and add it to the α-Al2O3 powder for granulation; Step 4: Dry-press the granulated powder in Step 3, the forming pressure is 18 MPa, obtain the green body, place it in an oven and keep it warm at 80 °C for 45 min; Step 5: Calcinate the green body dried in Step 4, the firing temperature is 1350 °C, the heating rate is 2 °C / min, and the holding time is 30 min.

[0032] The particle size of the white α-Al2O3 powder prepared in Step 1 is 2 μm, the specific surface area is 5 m 2 / g, the average pore diameter is 45 nm, its morphology is sheet-like hexagonal, and they are interlocked with each other, and the aspect ratio is about 10:1.

[0033] The alumina content of the α-Al2O3 ceramic prepared in Step 5 is 99.25 wt%, the density is 3.62 g / cm 3 , the shrinkage rate is 1.2%, and the flexural strength is 219 MPa.

[0034] The mass percentage composition of the above aluminum sol is: 20.243 wt% Al2O3, 0.012 wt% SiO2, 0.003 wt% Fe2O3, 0.012 wt% Na2O, 79.73 wt% ethanol organic solvent.

[0035] The above embodiments only illustratively explain the principle and efficacy of the present invention and some applied embodiments, rather than limiting the present invention; it should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature sintered high-purity alumina ceramic, characterized in that It includes the following steps: Step 1: Dissolve aluminum sol, sodium sulfate, and aluminum fluoride in water according to mass percentages to obtain a suspension. After the suspension undergoes heating, stirring, drying, grinding, sieving, and calcination processes, α-Al2O3 powder is obtained; Step 2: After the α-Al2O3 powder prepared in Step 1 undergoes grinding, sieving, granulation, forming, drying, and calcination processes, α-Al2O3 ceramic is obtained; In Step 1, the mass ratio of aluminum sol, sodium sulfate, aluminum fluoride, and water is 1:1 - 3:0.08 - 0.18:1 - 2; The mass percentage composition of the aluminum sol is: 20.243 wt% Al2O3, 0.012 wt% SiO2, 0.003 wt% Fe2O3, 0.012 wt% Na2O, 79.73 wt% ethanol organic solvent; In Step 1, the temperature of the calcination process is 1000 - 1200 °C, the heat preservation time is 1 - 3 h, and the heating rate is 3 - 5 °C / min.

2. The preparation method according to claim 1, characterized in that: In Step 1, the temperature of the heating and stirring process is 60 - 95 °C; the temperature of the drying process is 80 - 100 °C, and the heat preservation time is 5 - 8 h; the sieving process is through a 200 - 325 mesh sieve.

3. The preparation method according to claim 1, characterized in that: In Step 2, the sieving process is through a 350 - 400 mesh sieve; the forming process is dry pressing, and the pressure is 18 - 21 MPa; the temperature of the drying process is 60 - 100 °C, and the heat preservation time is 30 - 45 min.

4. The preparation method according to claim 1, characterized in that: In the granulation process of Step 2, PVA is added as a binder, and its mass is 1 - 3% of the α-Al2O3 powder, and the mass concentration is 3 - 5%.

5. The preparation method according to claim 1, characterized in that: In Step 2, the firing temperature of the calcination process is 1350 °C, the heating rate is 2 - 10 °C / min, and the heat preservation time is 30 - 120 min.

6. The preparation method according to claim 1, characterized in that: In the first step, the particle size of the α-Al2O3 powder is 1-5 μm, the specific surface area is 1-5 m 2 / g, the average pore diameter is 45-60 nm, the morphology is flaky hexagonal, the powders are interlocked with each other, and the aspect ratio of diameter to thickness is 8-10:

1.

7. The preparation method according to claim 1, characterized in that: In the second step, the alumina content of the α-Al2O3 ceramic is 98.55 to 99.25 wt%, the density is 3.59 to 3.62 g / cm 3 , the shrinkage rate is 1 to 1.2%, and the flexural strength is 204 to 219 MPa.

Citation Information

Patent Citations

  • Method for preparing aluminum oxide foamed ceramics through self-gelling and shaping of aluminium sol

    CN108863435A

  • Flaky alpha alumina and preparation method thereof

    CN114715925A

  • Preparation method of self-toughening high-flux plate-shaped porous ceramic supported molecular sieve membrane

    CN117105642A

  • Method for preparing flaky alumina by using alumina sol and controlling thickness

    CN117819582A

  • Preparation method of ceramic membrane support

    US20180029941A1